Osteoporosis among Fallers without Concomitant Fracture Identified in an Emergency Department: Frequencies and Risk Factors - Bente Glintborg; Ulrik Hesse; Thomas Houe; Jensen Claus Munk; Jan Pødenphant; Bo Zerahn (Advances in Orthopedics)
We aimed to determine whether the Emergency Department (ED) is a suitable entrance point for osteoporosis screening among fallers without concomitant fracture compared to referral from general practice. Furthermore, to identify factors associated with osteoporosis among fallers. Methods. Patients aged 50–80 years sustaining a low-energy fall without fracture were identified from an ED (n=199). Patients answered a questionnaire on risk factors and underwent osteodensitometry. Data was compared to a group of patients routinely referred to osteodensitometry from general practice (n=201). Results. Among the 199 included fallers, 41 (21%) had osteoporosis. Among these, 35 (85%) reported either previous fracture or reduced body height (>3 cm). These two risk factors were more frequent among fallers with osteoporosis compared to fallers with normal bone mineral density or osteopenia (previous fracture P=.044, height reduction P=.0016). The osteoporosis frequency among fallers from ED did not differ from a similarly aged patient-group referred from general practice (P=.34). Conclusion. Osteodensitometry should be considered among fallers without fracture presenting in the ED, especially if the patient has a prior fracture or declined body height. Since fallers generally have higher fracture risk, the ED might serve as an additional entrance to osteodensitometry compared to referral from primary care.